Molecular Insights Into Binding and Activation of the Human KCNQ2 Channel by Retigabine - Garofalo, Barbara; Bonvin, Alexandre M.J.J.; Bosin, Andrea; Di Giorgio, Francesco P.; Ombrato, Rosella; Vargiu, Attilio V. (Frontiers in Molecular Biosciences, 2022)
Voltage-gated potassium channels of the KV7.x family are involved in a plethora of biological processes across many tissues in animals, and their misfunctioning could lead to several pathologies ranging from diseases caused by neuronal hyperexcitability, such as epilepsy, or traumatic injuries and painful diabetic neuropathy to autoimmune disorders. Among the members of this family, the KV7.2 channel can form hetero-tetramers together with KV7.3, forming the so-called M-channels, which are primary regulators of intrinsic electrical properties of neurons and of their responsiveness to synaptic inputs. Here, prompted by the similarity between the M-current and that in KV7.2 alone, we perform a computational-based characterization of KV7.2 in its different conformational states and in complex with the modulator retigabine. After validation of the structural models of the channel by comparison with experimental data, we investigate the effect of retigabine binding on the two extreme states of KV7.2 (resting-closed and activated-open). Our results suggest that binding, so far structurally characterized only in the intermediate activated-closed state, is possible also in the other two functional states. Moreover, we show that some effects of this binding, such as increased flexibility of voltage sensing domains and propensity of the pore for open conformations, are virtually independent on the conformational state of the protein. Overall, our results provide new structural and dynamic insights into the functioning and the modulation of KV7.2 and related channels.